Environmental Protection In International Humanitarian Law - Erlies Septiana Nurbani (Faculty of Law, University of Mataram, 2018)
Environment, whether directly or indirectly is a casualty of armed conflict. As occured in Vietnam War 1961-1975, Gulf War 1991, Cosovo Conflct 1999, Iraqi War 2003 and Israel-Lebanon War 2006. UNEP concluded that armed conflict arise dangerous consequences to the environment. Environmental damage after warfare is often irreversible because the states think that environmental damage is an unavoidable consequence in order to achieve military targets. This research aims are to search international treaty and general principles in international humanitarian law that regulated environment protection during the armed conflict. Based on the research result it can be known that environment protection during the armed conflict has already regulated completely in international humanitarian law, not only in general agreement of humanitarian law (hag laws and geneva laws) but also in special agreement on environment protection during armed conflict, in the form of restriction on means and weapons that can be used in armed conflict. The regulation and enforcement of environment protection can be rely on general principles of international humanitarian law.